An institutional experience of 26 patients with Moyamoya disease: A study from Northwest India - Srivastava, Trilochan (Medknow Publications & Media Pvt Ltd, 2014)
AIM: Moyamoya disease (MMD) is a slowly progressive bilateral stenocclusive process of the distal internal carotid and proximal portions of the anterior and middle cerebral arteries and the formation of an abnormal vascular network at the base of the brain. The purpose of this retrospective study was to identify clinical features, salient features, radiological features and yield of diagnostic cerebral angiography in MMD. MATERIALS AND METHODS: We analyzed the records of 26 patients with MMD evaluated and treated at our institute from August 2010 until March 2013. Diagnosis of MMD was made on the basis of features of angiographic findings. Cerebral angiography showed typically fine network of vessels at the base of the brain with puff of smoke appearance suggestive of MMD. CT angiography (CTA) was done in 25 (96.15%) patients where as Digital substraction angiography (DSA) was done in 18 (69.23%) patients. RESULTS: Out of the 26 patients 13 were in the pediatric age group and 13 were adults. At presentation 14 patients had infarcts and 10 patients had hemorrhages. Among the hemorrhagic group 20% had isolated intracerebral hemorrhage (ICH), 50% patients had ICH with intraventricular extension (IVE) and 30% patients had primary intraventricular hemorrhage (PIVH). 50 % of the patients had involvement of the posterior circulation. CONCLUSION: Posterior circulation involvement is frequent in MMD. Though parenchymal bleed with/without intraventricular extension is the usual presentation of hemorrhagic MMD, isolated intraventricular hemorrhage could also be the mode of presentation.